Gastric volvulus or just a large stomach? a case report with literature review of gastric volvulus and gastrointestinal pathology in acromegaly - Mui, Jasmine J.; Sarkar, Amit; Magdy, Mark (International Surgery Journal, 2020)
Gastric volvulus is a surgical emergency that requires prompt recognition and management. The acromegalic patient has a number of pathophysiological factors that predispose to gastric volvulus and slow gastrointestinal (GI) transit. Authors aimed to present a case of hiatus hernia and gastric volvulus in a patient with acromegaly and review the current literature on GI anomalies in this population. A 70-year-old female presented to our institute with epigastric pain and coffee-ground vomiting on the background of acromegaly secondary to pituitary adenoma (resected in 1997). She was found to have a gastric volvulus and hiatus hernia which was repaired laparoscopically. She was discharged home but re-presented six days later with abdominal distension and vomiting. Computed tomography (CT) scan of abdomen showed recurrent gastric volvulus with involvement of the transverse colon. She underwent a laparotomy but no evidence of gastric or colonic volvulus was seen intra-operatively. The CT findings were attributed to a large stomach and coiled redundant transverse colon which could be misinterpreted as volvulus on imaging. Gastroparesis and slow bowel transit were the likely aetiology of this second presentation. This is consistent with literature reporting slow bowel transit and dolichocolon in acromegalic patients. Gastric volvulus is a rare finding associated with acromegaly. Structural anomalies in the anatomy of the acromegalic patient can make CT diagnosis challenging. This case demonstrates the need for caution when interpreting imaging in this cohort, as well as the need for further research on GI pathology associated with acromegaly.